محاكمة مجرمي الحرب بين القانون الدولي والشريعة الإسلامية : دراسة تحليلية - Berkane, Mesaoud Ben Saleh (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This study aim to compare between international law and Islamic law on the aspect of “War Crimes” and their perpetrators. I have adopted for this research an analytical study as the main method, besides other methods, namely inductive and comparative. The research focuses on determine the term of War Crimes in both International law and Islamic law. Then, it endeavour to state the different types of war crimes as defined by the competent bodies of the various laws and treaties, and the like this in Islamic law (sari'ah). In addition to outlines similarities and differences between international law and Islamic law in war crimes. And also discusses the ways how to prosecute war criminals under international law and Islamic law. The research concluded with some significant results and some recommendations that serve the related topic -The Prosecution of War Criminals Between International Law and Islamic Law (analytical study) - and its subjects, which highlight the concept of war crimes, and the difference between war crimes in both legislation, and the reasons for disabling force of justice among human beings, as well as some appendices for this topic.